PREDIKSI LABA MASA DEPAN DENGAN FUTURE EARNINGS RESPONSE COEFFISIENT MELALUI MANAJEMEN LABA - Gustin Padwa Sari; Febriyanto Febriyanto (Jurnal Akuntansi dan Keuangan, 2019)
This study aims to examine whether accrual earnings management, real earnings management and income smoothing by the company influences the ability of market to predict the company's future earnings as measured by future earnings response coefficient (FERC). The study uses a sample of manufacturing company during 2014-2016 by using the purposive sampling method. Based on analysis result, the accrual earnings management does not affect the ability of market to predict future earnings; real earnings management does not affect the ability of market to predict future earnings; and earnings management that uses income smoothing affects the ability of market to predict future earnings.